Sputter-instigated plasmon-enhanced optical backscattering layer in ultrathin solar cells: Application of GZO in CIGSe material system. (1st November 2018) - Garg, Vivek; Sengar, Brajendra S.; Sharma, Pankaj; Kumar, Amitesh; Aaryashree,; Kumar, Shailendra; Mukherjee, Shaibal
Highlights: Verification of plasmonic behavior in GZO film (∼150 nm). Checking on the sustainability of such plasmonic behavior in ultrathin GZO (∼5 nm). Investigation of plasmonic feature at the heterojunction. Band offset studies at the plasmon-enhanced-GZO/CIGSe heterojunction. J-V analysis at the junction to verify the linear behavior and resistivity estimation. Abstract: Recently, realization of ultrathin solar cells is the area of interest of researchers in the domain of cost-effective photovoltaics. This study demonstrates a novel way of generation of plasmonic features in transparent conducting oxide material in the form of Ga-doped ZnO (GZO) thin films to compensate for the loss of optical absorption due to reduced absorber thickness. Through an extensive analysis of photoelectron spectroscopy, spectroscopic ellipsometry, and field emission scanning electron microscope measurements the evaluation of plasmonic features and correlation of them with various metallic and metal-oxide nanoclusters inside GZO thin film and GZO/CIGSe heterojunction interface are carried out. Moreover, we have thoroughly analyzed the applicability of GZO plasmon enhanced thin film as a backscattering layer based on (a) verification of plasmonic behavior in GZO film (∼150 nm), (b) checking on the sustainability of such plasmonic behavior in ultrathin GZO (∼5 nm) layer, (c) investigation of plasmonic feature at the heterojunction, (d) band offset studies at the plasmon-enhanced-GZO/CIGSe heterojunction, and (e) investigating the electrical performance of the junction to verify the linear behavior and resistivity calculation of the heterojunction.